Interspecies transformation in Bacillus: sequence heterology as the major barrier. - Harris-Warrick, R M (1978)
The relative contribution of DNA restriction and of sequence heterology as barriers to interspecies transfer of DNA was studied in the heterologous transformation of Bacillus subtilis recipients by DNA was studied in the heterologous transformation of Bacillus subtilis recipients by DNA isolated from B. globigii. Transformants were obtained at very low frequencies in the evolutionarily nonconserved aromatic region; high cotransfer of linked markers was observed. New mutations were introduced into the B. globigii intergenote sequence in the resulting hybrids; these markers could be transformed with high efficiency by both B. globigii and B. subtilis DNA, representing a 10(5)-fold increase in heterologous transforming efficiency. A restriction activity in B. globigii crude extracts inactivated the biological activity of B. subtilis and hybrid DNA but not B. globigii DNA in vitro, demonstrating different sites for restriction and modification between these species. In vivo, however, B. globigii and hybrid DNA transformed the B. globigii sequence in a hybrid recipient with the same efficiency. These results show that sequence heterology is the major barrier to interspecies transformation and that, in this system, enzymatic restriction does not prevent interspecies transformation.